Clinical outcome in patients from a single region who were dependent on parenteral nutrition for 28 days or more. Issue 4 (11th January 2008) - Köglmeier, J; Day, C; Puntis, J W L
Abstract : Background: The frequency and outcome of intestinal failure (IF) in children are not well defined in the UK. Long-term parenteral nutrition (PN) is an effective intervention, with intestine transplantation offering the possibility of survival should life-threatening complications arise in those with long-term dependency. The ideal model for service provision is a subject of debate. Aims: We aimed to identify all new cases of IF (defined as PN dependency ⩾28 days) in West Yorkshire over a two-year period to determine the rate of serious complications, establish the outcome after two years and clarify the role of specialist referral. Method: Pharmacists in all the West Yorkshire paediatric units were contacted to establish the number of children with IF during 2001–2002. Underlying diagnosis, complications and outcome at two years were obtained by case-note review for 93 of the 96 children identified. Results: IF patients were exclusively managed in one or other of the three large teaching hospitals. At the two-year follow-up, six (6.4%) children had died (one while listed for a small bowel transplantation), but 85 (91%) had established full enteral feeding and were well. Two remained PN dependent and were assessed in the supra-regional intestinal transplantation unit (Birmingham); in neither case was small bowel transplantation thought to be appropriate. The most common complications were central venous catheter sepsis (69% of patients) and cholestasis (59%). Conclusions: This study shows that a favourable outcome for IF can be achieved in a regional centre with appropriate multidisciplinary support. A single UK supra-regional unit undertaking small bowel transplantation is probably adequate for assessment of the most complex patients, although this should remain under review.